2014
DOI: 10.7314/apjcp.2014.15.10.4325
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oral Pre-malignant Lesions and its Risk Factors in an Indian Subcontinent Low Income Migrant Group in Qatar

Abstract: Background: The expatriate population in Qatar largely comprises workers from the Indian subcontinent which has a very high rate of oral malignancy. Social and cultural habits and as well premalignant risk factors in this population remain prevalent even after migration. Materials and Methods: This cross sectional study assessed the prevalence of risk factors and occurrence of oral precancerous lesions in a low income group expatriate community from the Indian subcontinent residing in Qatar. Results: Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…In such situations, it is difficult to know the independent effect of each habit. Chewing habit, like smoking, has been proven to be associated with premalignant oral lesions (Kavarodi et al, 2014). Majority of the habits seen here were similar to the habits seen in other parts of the country with chewers exceeding smokers.…”
Section: Discussionsupporting
confidence: 75%
“…In such situations, it is difficult to know the independent effect of each habit. Chewing habit, like smoking, has been proven to be associated with premalignant oral lesions (Kavarodi et al, 2014). Majority of the habits seen here were similar to the habits seen in other parts of the country with chewers exceeding smokers.…”
Section: Discussionsupporting
confidence: 75%
“…The most frequent lesions include leukoplakia, lichen planus, erythroplakia and oral submucous fibrosis. Studies have shown that up to 18% of oral precancer develops into oral cancer 2,3 . Early detection of premalignant conditions can improve the prognosis and help in disease prevention.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Clinical prevalence of oral lesions among migrant workers was found to be 4.6%. 19 Third study looked at the chronic kidney disease among workers and found that 13.6% of workers had diabetic nephropathy. 37 In the study by Pradhan et al, 35 cardiovascular disease, natural/others reasons and murder contributed to 42%, 25% and 1.7% of deaths, respectively.…”
Section: Resultsmentioning
confidence: 99%